Treprostinil Attains Clinically Therapeutic Concentrations in Neonates with Pulmonary Hypertension on Extracorporeal Membrane Oxygenation Support. Issue 10 (16th September 2020) - De Bie, Felix R.; Allegaert, Karel; Hedrick, Holly L.; Rintoul, Natalie E.; Davidson, Alexander
Abstract : Background: Treprostinil is a prostacyclin analog used for treatment of pulmonary hypertension (PH) in adults and children, currently awaiting clinical assessment for use in neonates: Objectives: We aimed to investigate the use of treprostinil in neonates with PH on extracorporeal membrane oxygenation (ECMO) support and measure plasma concentrations of the drug: Methods: This is a retrospective case‐series with prospectively collected blood samples, conducted in a quaternary care neonatal intensive care unit. Brain natriuretic peptide, cardiac function on Doppler echocardiography, and the occurrence of adverse effects was monitored. Plasma concentrations were measured using high‐performance liquid chromatography and mass spectrometry: Results: Four patients with PH requiring ECMO therapy were studied. Treprostinil doses of 20–58 ng/kg/min reached concentrations of 0.99–4.39 ng/ml and induced clinical improvement. Infusion of treprostinil was associated with improved right ventricular function, reversed right‐to‐left shunting through the ductus arteriosus, and stable or decreasing need for vasopressor support. No adverse effects were observed: Conclusions: This is the first study to report clinically therapeutic treprostinil concentrations in circulating plasma after treprostinil administration in neonates on ECMO, with associated clinical improvement of PH and no signs of hemodynamic instability: